Navigating the matrix: career development and the responsibilisation of employability in Australia. Issue 4 (4th July 2022) - Rice, Suzanne; Leahy, Mary; Klatt, Gosia
ABSTRACT: In this paper we seek to understand how structural, contextual and institutional conditions influence the construction of individual agency in career development policy. We focus on responsibilisation, the process by which responsibility for outcomes is transferred from the state to the individual, through a combination of policy actions and the framing of public discourse. We use Australia as a case study to examine how the state has recast its role in the creation and regulation of employment. We outline how the role of the state now involves guiding the citizen towards the "right choice", with individuals responsible for and active managers of risk in the labour market. To determine the complex narratives around agency, we examine the assumptions embedded in some current Australian government career guidance websites, to highlight how jobseeker autonomy, self-direction, agency, and self-management are framed. The implications for socially just career development provision are discussed.